Studies on Oocyte Development in Blue Gourami (Trichogaster trichopterus) Fry Involves Several Stages - Gad Degani (Advanced Research in Biological Science Vol. 2, 2023)
We investigated the early stages of ovarian development and the levels of estradiol-17\(β\) (E2) and gonadal CYP19 (bgCYP19a) in blue gourami fish (Trichogaster trichopterus). Samples of larvae were collected at 38, 55, and 80 days after hatching for histological examination. Ovary size and number of oocytes were smaller in 38-day larvae than in 80-day larvae. All oocytes were in the perinuclear stage on day 38, but some of them had entered vitellogenesis by day 80. The mRNA expression of bgCYP19a was measured by real-time PCR in tissues from 38- and 80-day larvae. There was no significant change in expression level between the two time points. However, E2 levels were significantly higher in 80-day vs. 38-day larvae.